(untitled) (Global Journal of Management and Business Research, 2015)
A new business, is more of a gamble. The owner has no idea how the business will perform since it has no past history or customer loyalty. The owner must provide physical facilities, inventories and organization as well as create an image for the business and assume it’s risks. There are certain advantages to doing this. The new firm is designed specially by the entrepreneur. Location is selected; not merely accepted because it is already there. The fixtures, equipment, inventories, employees serve the needs of the owner. Although all customers are new and must be attracted to the business, there is no chance of inheriting a poor reputation from the owner.